2016
DOI: 10.1103/physrevapplied.6.034016
|View full text |Cite
|
Sign up to set email alerts
|

Using Atom-Probe Tomography to UnderstandZnOAl/SiO2/SiSchottky Diodes

Abstract: We use electronic transport and atom-probe tomography to study ZnO∶Al=SiO 2 =Si Schottky diodes on lightly doped n-and p-type Si. We vary the carrier concentration in the ZnO∶Al films by 2 orders of magnitude, but the Schottky barrier height remains nearly constant. Atom-probe tomography shows that Al segregates to the interface, so that the ZnO∶Al at the junction is likely to be metallic even when the bulk of the ZnO∶Al film is semiconducting. We hypothesize that the observed Fermi-level pinning is connected … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…The latter is a tool for 3D imaging of the composition of thin films at the atomic scale, which is found to be particularly powerful for doped films. 16 19 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is a tool for 3D imaging of the composition of thin films at the atomic scale, which is found to be particularly powerful for doped films. 16 19 …”
Section: Introductionmentioning
confidence: 99%
“…The spatial distribution of the Al atoms was obtained at an atomic resolution by transmission electron microscopy (TEM) and atom probe tomography (APT). The latter is a tool for 3D imaging of the composition of thin films at the atomic scale, which is found to be particularly powerful for doped films. …”
Section: Introductionmentioning
confidence: 99%
“…Study concerning the band offset and the Fermi level position at the interface of ZnO/Si is also necessary, since charge transfer and recombination activity depend on these factors . Jaramillo et al have recently related conductive oxide/Si interface with metal/Si Schottky junction in terms of Fermi level pinning . Using electronic transport and atom‐probe tomography, they have demonstrated that the Fermi level is pinned in the lower half of the Si bandgap at ZnO:Al/SiO 2 /Si Schottky junction.…”
Section: Discussionmentioning
confidence: 99%
“…[ 112–133 ] d) Measured Schottky barrier heights of different TCOs, CBMs, and TMOs. [ 134–141 ] X‐ray photoelectron spectroscopy (XPS) spectra of e) nondoped, f) V‐doped, and g) Nb‐doped MoO 3− x films. Reproduced with permission.…”
Section: Characterization Of Dfpc Materials With Key Parametersmentioning
confidence: 99%
“…c) Bandgap diagrams and work function positions (dashed lines) of different TCOs, CBMs, TMOs, and FCMs with the c-Si energy band edges (gray bar) as a reference. d) Measured Schottky barrier heights of different TCOs, CBMs, and TMOs [134][135][136][137][138][139][140][141]. X-ray photoelectron spectroscopy (XPS) spectra of e) nondoped, f ) V-doped, and g) Nb-doped MoO 3Àx films.…”
mentioning
confidence: 99%